The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3906/sag-1312-130
|View full text |Cite
|
Sign up to set email alerts
|

Hypo- and hypervolemic edema in children with steroidsensitive nephrotic syndrome

Abstract: Background/aim: The mechanism of edema formation in nephrotic syndrome is still poorly understood. We aimed to evaluate the volume status in children with steroid-sensitive nephrotic syndrome (SSNS) and to emphasize the importance of echocardiography in demonstrating of volume changes.Materials and methods: Thirty-two SSNS patients and 30 healthy children were enrolled in this study. The volume statuses of patients were evaluated by clinical and laboratory features, including fractional sodium excretion (FENa)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…However, in phase 2 of their study, the FeNa% criterion for the volume status was modi ed and patients with FeNa% of < 0.2% were identi ed with volume contraction which we have applied in addition to clinical assessment to differentiate edema types. In the current work,73.3% of the studied patients were non-hypovolemic; the same observation was noted by Buyukavci and colleagues [7] who reported that 75% of their patients were non-hypovolemic and another study also in 2015, by Ozdemir [9] studied NS subgroups (relapse-edematous, relapse-edema free and remission), were compared. They found nonsigni cant difference between groups as regard to IVCCI.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…However, in phase 2 of their study, the FeNa% criterion for the volume status was modi ed and patients with FeNa% of < 0.2% were identi ed with volume contraction which we have applied in addition to clinical assessment to differentiate edema types. In the current work,73.3% of the studied patients were non-hypovolemic; the same observation was noted by Buyukavci and colleagues [7] who reported that 75% of their patients were non-hypovolemic and another study also in 2015, by Ozdemir [9] studied NS subgroups (relapse-edematous, relapse-edema free and remission), were compared. They found nonsigni cant difference between groups as regard to IVCCI.…”
Section: Resultssupporting
confidence: 78%
“…Some literatures relied on the presence or absence of hypovolemic symptoms and signs [4] or radioactive labeling techniques [5]. Later researches explored the roles of inferior vena cava collapsibility index (IVCCI) and left atrial diameter (LAD) assessed by echocardiography (ECHO) [6,7] and over hydration (OH) value assessed by bioimpedance spectroscopy (BIS) technique such as body composition monitor (BCM) [8] for volume burden assessment. IVCCI has strong correlation to central venous pressure so it decreases with increased intra vascular volume and have been widely used for volume status assessment in hemodialysis and critically ill patients and less frequently in INS [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with severe edema have marked hypoalbuminemia (serum albumin <1.5 g/dL), along with ascites and anasarca that interferes with daily activities [97,98]. Intravascular volume depletion is common in patients with moderate or severe edema [99,100], and should be assessed before instituting therapy with diuretics.…”
Section: Guideline 6: Management Of Hypovolemia and Edemamentioning
confidence: 99%
“…2). Subsequently, patients are managed with IV and oral hydration, and IV albumin (20%; 0.5-1 g/kg over 3-4 hr) [97,99,101].…”
Section: Hypovolemiamentioning
confidence: 99%